2012
DOI: 10.1002/mats.201200056
|View full text |Cite
|
Sign up to set email alerts
|

Void Microstructuring in Lamellar Phase of Amphiphilic Macromolecules

Abstract: The free volume (voids) distribution in the lamellae of the conventional symmetric and amphiphilic diblock copolymers is studied via Monte–Carlo simulation based on the standard bond fluctuation model. Both in the conventional and amphiphilic block copolymers the voids are found to concentrate on the interfaces between the incompatible units, the magnitude of the effect being unexpectedly significant. A crystalline‐like ordering of voids with increase of the incompatibility between the different repeated units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…34 It was shown that such a model allows to describe the unique conformations adopted by macromolecules with amphiphilic monomer units in dilute and concentrated solutions, 3439 to reconstruct their specific ordering in the bulk 40,41 and near interface. 4244 In selective solvent, amphiphilic homopolymers sparsely grafted onto a flat substrate can form an ultrathin coating having the width of about two monomer units. 29 Domains oriented perpendicularly to the substrate are observed in densely grafted amphiphilic homopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…34 It was shown that such a model allows to describe the unique conformations adopted by macromolecules with amphiphilic monomer units in dilute and concentrated solutions, 3439 to reconstruct their specific ordering in the bulk 40,41 and near interface. 4244 In selective solvent, amphiphilic homopolymers sparsely grafted onto a flat substrate can form an ultrathin coating having the width of about two monomer units. 29 Domains oriented perpendicularly to the substrate are observed in densely grafted amphiphilic homopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular simulations such as molecular dynamics and coarse‐grained models have been extensively used to analyze both the static and dynamic properties of polymeric materials. By simplifying detailed chemistry and atomic details, coarse‐grained models provide both computational and conceptual advantages that facilitate numerical calculations and theoretical analyses of complex phenomena .…”
Section: Introductionmentioning
confidence: 99%
“…The voids are found to concentrate on the interfaces and to perform crystalline-like ordering in case of significant amphiphilicity of units. 40 The theoretical study 41,42 of morphological states of macromolecules with amphiphilic monomer units shows that the crucial factor stabilizing the shape of macromolecules in a condensed globular state is the surface tension decrease due to the polar group orientation towards the external solution.…”
Section: Introductionmentioning
confidence: 99%